Aplikasi Panduan Wisata Belanja Menggunakan Indoor Maps Berbasis Android Di Surabaya ( Studi Kasus : Dinas Kebudayaan dan Pariwisata Surabaya) - Tristiantoro, Heri; Sutanto, Teguh; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2012)
Surabaya has great potential in the field of tourism, one corresponding to the tourism potential of Surabaya is a shopping tour. The emergence of various shopping malls and entertainment facilities are diverse, can be one of the biggest assets for Surabaya to turn into the City Shopping Tour. City Government (City Government) Surabaya, which this year plans to increase the attraction Surabaya, was not accompanied by step guide wisata.Sehingga increasing number of tourists who travel to Surabaya less informative about where and what can be obtained as a shopping tour of Surabaya. Shopping information retrieval applications in android based mobile by using the indoor map, which is a technology that uses the internet and mobile phones to access the required information to the tenant level. Today, the Internet and mobile phones are many who use it, so for applications that supported the implementation of Internet and mobile android is very important With the applications that implement the use of mobile-based technology and supported features android indoor map, is expected to solve problems and provide ease of information for tourists who want to find information on a shopping tour promo, event, tenant, products offered and tenant site plan without having to depend at the time and location as they are accessed. Keywords: mall, belanja, wisata, indoor maps, ericsson labs, maps